Legal Analysis of the Mainland and Hong Kong Closer Economic Cooperation Partnership Agreement (2003) - N. V. Veremeyev (Московский журнал международного права, 2012)
Mainland and Hong Kong Closer Economic Partnership Arrangement (CEPA), singed between the People’s Republic of China and Hong Kong in late 2003, became the first ever free trade deal for the both parties. CEPA is an international agreement, subjected to international (WTO) law, between the central government of China and the government of one of the China’s special administrative regions. This distinguishes the Arrangement from a myriad of other regional trade agreements (RTA). CEPA focuses on liberalization of trade in goods and services between China and Hong Kong. The Arrangement generally complies with relevant WTO provisions and covers areas of trade not governed by WTO agreements (WTO-plus). Moreover, in some respects CEPA goes far beyond trade liberalization agenda of many RTAs. CEPA demonstrates China’s intention to neutralize those excessive and arguably discriminatory conditions, accepted by her upon admission to the WTO, through the insertion of more favorable rules in her trade agreements with other WTO members.